3D printing CFD simulation results using structural mechanics. Issue 3 (9th April 2020) - Takeda, Hiroki; Ohtake, Yutaka; Suzuki, Hiromasa
Abstract: Good visualizations of computational fluid dynamics (CFD) results are key to making the best use of them. In many cases, CFD results involve multidimensional data embedded in 3D, and it can be difficult to recognize such complicated 3D shapes when they are projected onto 2D displays. A promising alternative approach uses a 3D printer to build real objects representing the CFD results. In this paper, we present a method of 3D printing the isosurfaces of CFD results to visualize them. However, there is a problem that the isosurfaces are not connected. Therefore, to prevent the structure from breaking up, we must find a way to connect them, and we achieve this by using beams to generate a support structure. We take a structural mechanics approach, using an algorithm to optimize the support structure such that the printed object does not break under gravity, enabling us to hold it safely for observation. Graphical Abstract: